Javanese-Indonesian Female Facial Expression (JIFFE-3D) Based on 3D Marker - Muhtadin Muhtadin; Surya Sumpeno; Hosyi’ah Rusdiana (IPTEK Journal of Proceedings Series, 2014)
Facial expression is a topic which is frequently used in several areas of research, such as security, psychology, and entertainment. All of these researches demand a high quality source data of facial expression. This research builds Javanese-Indonesian Female Facial Expression Database in three dimensional data called JIFFE-3D Database. JIFFE-3D Database contains facial expression which expresses Javanese-Indonesian female universal emotions, such as happiness, disgust, fear, angry, surprise, and sadness. JIFFE-3D Database is made by using motion capture system to capture changes in facial expression which is characterized by a shift in markers on face. The facial expression is captured by multi camera and saved in 3D data. JIFFE-3D Database could be a high quality source data if all data use only marker which has influence the shifting in facial expression.